2015
DOI: 10.1007/s00520-015-2983-3
|View full text |Cite
|
Sign up to set email alerts
|

Computerized patient-reported symptom assessment in radiotherapy: a pilot randomized, controlled trial

Abstract: Purpose Computer-based, patient-reported symptom survey tools have been described for patients undergoing chemotherapy. We hypothesized that patients undergoing radiotherapy might also benefit, so we developed a computer application to acquire symptom ratings from patients and generate summaries for use at point of care office visits and conducted a randomized-controlled pilot trial to test its feasibility. Methods Subjects were randomized prior to beginning radiotherapy. Both control and intervention group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…40 Effect sizes of 0.01-0.21 for between group differences in MSAS global distress index were reported in a randomised controlled trial of computerised patient reported symptom monitoring during one to four weeks of radiotherapy. 41 eSMART showed significant improvements in anxiety, health related quality of life, self-efficacy, and supportive care needs in the intervention group. The improvements in health related quality of life are consistent with findings from recent trials using remote monitoring systems in chemotherapy care.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…40 Effect sizes of 0.01-0.21 for between group differences in MSAS global distress index were reported in a randomised controlled trial of computerised patient reported symptom monitoring during one to four weeks of radiotherapy. 41 eSMART showed significant improvements in anxiety, health related quality of life, self-efficacy, and supportive care needs in the intervention group. The improvements in health related quality of life are consistent with findings from recent trials using remote monitoring systems in chemotherapy care.…”
Section: Discussionmentioning
confidence: 90%
“…In a randomised controlled trial testing a symptom monitoring app during neoadjuvant chemotherapy for breast cancer, Fjell et al reported an effect size of 0.26 for between group differences in total MSAS (and 0.34 for MSAS global distress index scores) two weeks after treatment completion 40. Effect sizes of 0.01-0.21 for between group differences in MSAS global distress index were reported in a randomised controlled trial of computerised patient reported symptom monitoring during one to four weeks of radiotherapy 41…”
Section: Discussionmentioning
confidence: 99%
“…The study characteristics table (https://cdn. amegroups.cn/static/public/jhmhp-20-108-1.pdf) lists key characteristics of the included studies (38,(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68).…”
Section: Resultsmentioning
confidence: 99%
“…The CSS tool asks, “Did you find this survey to be helpful?” The majority of respondents answered yes to this question (18 = yes; 3 = no [2 males; 1 female]). It is also important to consider the patient perspective when evaluating the effectiveness of distress screening ( Chiang, Amport, Corjulo, Harvey, & McCorkle, 2015 ; Faller et al, 2016 ; Fromme et al, 2016 ). After screening, each participant received a minimum of one email or phone call to assess if they had attended a support group or other activity and if those referred for psychotherapy had accessed that referral.…”
Section: Methodsmentioning
confidence: 99%